2=10-3(x+7)+5(1-x)+6x

Simple and best practice solution for 2=10-3(x+7)+5(1-x)+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2=10-3(x+7)+5(1-x)+6x equation:



2=10-3(x+7)+5(1-x)+6x
We move all terms to the left:
2-(10-3(x+7)+5(1-x)+6x)=0
We add all the numbers together, and all the variables
-(10-3(x+7)+5(-1x+1)+6x)+2=0
We calculate terms in parentheses: -(10-3(x+7)+5(-1x+1)+6x), so:
10-3(x+7)+5(-1x+1)+6x
determiningTheFunctionDomain -3(x+7)+5(-1x+1)+6x+10
We add all the numbers together, and all the variables
6x-3(x+7)+5(-1x+1)+10
We multiply parentheses
6x-3x-5x-21+5+10
We add all the numbers together, and all the variables
-2x-6
Back to the equation:
-(-2x-6)
We get rid of parentheses
2x+6+2=0
We add all the numbers together, and all the variables
2x+8=0
We move all terms containing x to the left, all other terms to the right
2x=-8
x=-8/2
x=-4

You can always share this solution

See similar equations:

| X=7x-23 | | 4b÷8=20b= | | 4b÷8=20 | | 4.7x+2-4x=7+2x+4 | | 3-x/3=9/2 | | n+22=72 | | 8w?12=?5 | | (10x+9)=(4x+1) | | x^2?7x+2=0 | | 11x5=8x-6 | | 5(3m-2)-9(5-2m)=4m+2(5m+1) | | 2x2=300 | | 5(3m-2)-9(5-2m)=4m+2(5m+1 | | 3x+4=5-9 | | 9/x=98/7 | | 3x+17=32;3 | | 5x+3=15x+7 | | 261=152-v | | 5x+3+15x+7=180 | | 4x+5=17;3 | | 8/x^2-1-4/x-1=2/x+1 | | 23=3/1b–2+3/4b | | (4x-25)(2x-1)=180 | | 8y+–11y+8=17 | | -13+p=-10 | | 1.5x-(6)=7.5 | | 7x+4-2x=10x+16 | | 2x?3+4x=29 | | -x-20=6x+1 | | -4x-(18)=22 | | a+7-3(2a+5)=-2(a-15)-5 | | X+19=2x-20;-1 |

Equations solver categories